Galactose in dairy products - Abrahamson, Agnes (SLU/Dept. of Food Science, 2015)
Milk and milk consumption has been subject of discussion for a long time, and is still a hot topic. Recently, as study was published that observed a correlation between milk intake and increased risk of fractures and mortality. The authors proposed the milk’s content of D-galactose as the possible mechanism, since D-galactose is used indicated ageing in animal models. Therefore, this study aims to develop a method to determine the amount of galactose, glucose and lactose in milk and fermented milk and apply it on to dairy products on the Swedish market. Low-pasteurized milk, lac- tose free milk, UHT milk, yogurt, lactose free yogurt, Filmjölk, Onaka and A-fil were subjected to analysis, stored in different temperatures until their expiration date and sampled during this time period to analyse changes in carbohydrate content. A method for HPAE-PAD analysis, a method for quantification of carbohydrates, was developed using CarboPac SA10 column. The amount of galactose in milk is 7.12 mg/100 g. No changes in carbohydrate content could be observed, except for UHT milk stored at 30° C (12.22 mg/100 g) compared to 20° C (9.90 mg/100 g) and 4° C (9.39 mg/100 g) storage temperature. The amount of galactose in yogurt products are generally higher, compared to other types of fermented milks (1583.33 mg/100 g to 62.95 mg/100 g). The analysis method need further development regarding sample dilution.